GE_GERICHTE C/12969/2014 vom 25. September 2015 - GE Cour de justice (2015)
AUDITION DE L'ENFANT; DROIT DE GARDE; VISITE; OBLIGATION D'ENTRETIEN; ENFANT | CPC.298.1; CC.176.3; CC.273.1; CC.176.1; CC.163; CC.276.1